Educational capital and the role of informal education of youth from Cieszyn Silesia1 - Dyczek, Berenika (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to analyse the importance of educational capital. In post- communist societies such as Poland, the process of shaping the social structure is slightly different compared to societies such as France or England. In this situation, the role of education may turn out to be much more important in acquiring cultural capital. The research was carried out in Poland, in Cieszyn Silesia, in schools located in Cieszyn, Skoczów, Ustroń and Istebna between October 2012 and January 2013. The research group consisted of students from high schools and colleges . The year of birth of the students was between 1994- 1997. The total number of students of secondary schools in 2012/2013 was 5413. Survey results show that in Cieszyn Silesia, social capital acts as a kind of transmitter between inherited and acquired capital and helps acquire high educational capital.